2018
DOI: 10.1617/s11527-017-1130-7
|View full text |Cite
|
Sign up to set email alerts
|

A material-performance-based database for FRC and RC elements under shear loading

Abstract: The shear strength of elements reinforced by fibres is predicted by Codes using formulations generally developed from a limited set of test results. In fact, only few of available test results are combined with a material mechanical characterization, allowing to evaluate and compare the different performances of Fibre Reinforced Concretes (FRC). To address this problem, a material-performance-based shear database for FRC elements and their related reference samples in Reinforced Concrete (RC, with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 32 publications
(51 reference statements)
1
39
0
2
Order By: Relevance
“…Comparison between the proposed model and the experiments gave an absolute average error of 11.39% and a coefficient of variation of 15.42%. Other recent research works that have considered databases of experiments have used smaller databases than this study: 122 experiments [11] or 171 experiments (of which 93 with Fiber Reinforced Concrete) [44].…”
Section: Rdmentioning
confidence: 99%
“…Comparison between the proposed model and the experiments gave an absolute average error of 11.39% and a coefficient of variation of 15.42%. Other recent research works that have considered databases of experiments have used smaller databases than this study: 122 experiments [11] or 171 experiments (of which 93 with Fiber Reinforced Concrete) [44].…”
Section: Rdmentioning
confidence: 99%
“…To evaluate performance of the model the database developed for Foster et al [29] was expanded; additional tests included prestressed concrete members and beams reinforced with crimped (C), and flat end (FH) fibres, as well as high-strength (HS) fibres. A large database in this regards was also recently published in [30], which includes many of the beams considered . The test specimens used in this paper to test the design models are presented in Table 3.…”
Section: Model Assessment and Validationmentioning
confidence: 99%
“…Their study identified 413 SFRC beams reported in the literature as being tested in shear, although many of the tests were limited by their flexural strength. Recent articles have been dedicated to prepare substantive test databases in this subject [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The use of stirrups for shear resistance is a classical solution but relatively expensive because it is laborwork demanding; the use of FRC for shear resistance is one of the most analyzed structural application in research studies (Fig. 6) [34,35]. In fact, FRC enhances the shear resisting mechanisms in the beam.…”
Section: Shear In Linear Elements With Rebars As Bending Reinforcementmentioning
confidence: 99%